Cross-section measurements of the Higgs boson decaying into a pair of tau-leptons in proton-proton collisions at root s=13 TeV with the ATLAS detector - Onofre, A. (2019)
A measurement of production cross sections of the Higgs boson in proton-proton collisions is presented in the H→ττ decay channel. The analysis is performed using 36.1  fb−1 of data recorded by the ATLAS experiment at the Large Hadron Collider at a center-of-mass energy of √s=13  TeV. All combinations of leptonic (τ→ℓv¯v with ℓ=e,μ) and hadronic (τ→hadrons v) τ decays are considered. The H→ττ signal over the expected background from other Standard Model processes is established with an observed (expected) significance of 4.4 (4.1) standard deviations. Combined with results obtained using data taken at 7 and 8 TeV center-of-mass energies, the observed (expected) significance amounts to 6.4 (5.4) standard deviations and constitutes an observation of H→ττ decays. Using the data taken at √s=13  TeV, the total cross section in the H→ττ decay channel is measured to be 3.77+0.60−0.59 (stat) +0.87−0.74 (syst)  pb, for a Higgs boson of mass 125 GeV assuming the relative contributions of its production modes as predicted by the Standard Model. Total cross sections in the H→ττ decay channel are determined separately for vector-boson-fusion production and gluon-gluon-fusion production to be σVBFH→ττ=0.28±0.09 (stat) +0.11−0.09 (syst)  pb and σggFH→ττ=3.1±1.0 (stat) +1.6−1.3 (syst)  pb, respectively. Similarly, results of a fit are reported in the framework of simplified template cross sections. All measurements are in agreement with Standard Model expectations.